2010
DOI: 10.1007/s00248-010-9676-8
|View full text |Cite
|
Sign up to set email alerts
|

Fungi in Roots of Nursery Grown Pinus sylvestris: Ectomycorrhizal Colonisation, Genetic Diversity and Spatial Distribution

Abstract: The aims of this study were to investigate patterns of ectomycorrhizal (ECM) colonisation and community structure on nursery grown seedlings of Pinus sylvestris, spatial distribution of ECMs in the nursery plot and genetic diversity of commonly isolated ECM basidiomycete Hebeloma cavipes. One hundred seedlings were sampled in 225 m(2) area using a systematic grid design. For each seedling, 20 individual root tips were randomly collected, morphotyped, and surface sterilised for fungal isolation in pure culture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 46 publications
7
26
1
Order By: Relevance
“…For example, Voříšková et al [41] demonstrated that, in a temperate oak forest soil saprotrophic genera reached their seasonal maxima in autumn, while mycorrhizal taxa dominated in summer, suggesting that decomposition of organic matter and phytosynthate allocation represent important factors contributing to the community variations during the growing season. Despite the high fungal diversity, fungal community was dominated by a limited number of fungal taxa (Table 2) many of which were reported from forest nurseries before [14,15,22,39,42]. Therefore, our results corroborate previous observations and demonstrate specificity of fungal communities in forest nurseries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Voříšková et al [41] demonstrated that, in a temperate oak forest soil saprotrophic genera reached their seasonal maxima in autumn, while mycorrhizal taxa dominated in summer, suggesting that decomposition of organic matter and phytosynthate allocation represent important factors contributing to the community variations during the growing season. Despite the high fungal diversity, fungal community was dominated by a limited number of fungal taxa (Table 2) many of which were reported from forest nurseries before [14,15,22,39,42]. Therefore, our results corroborate previous observations and demonstrate specificity of fungal communities in forest nurseries.…”
Section: Discussionsupporting
confidence: 90%
“…Early detection of such diseases is critical as this can prevent further establishment and spread to new environments. In addition to detrimental pathogenic fungi, roots of tree seedlings harbor beneficial communities of fungi [14,15], which may promote seedling growth both in forest nurseries and after outplanting [16]. Mycorrhizal fungi are known to provide nutritional benefits to their hosts and may increase tolerance to abiotic and biotic stress factors [17].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings add to the evidence of a growing number of symbionts being able to colonize seedlings in nursery conditions, and emphasize the elucidation potential of molecular tools for detailed descriptions of ECM communities in different environments. Some of the identified fungi (Cenococcum, Tuber, Hebeloma, Laccaria) have been previously noted in forest nurseries as ECM symbionts of coniferous (Menkis et al 2005;Rudawska et al 2006;Leski et al 2008;Menkis and Vasaitis 2011) or deciduous hosts (Leski et al 2010), but some of them have been found for the first time in nursery conditions (Hydnotrya, Hymenogaster, Lactarius), or even as mycorrhizal partners of European beech (Naucoria, Geopora). For more details about the detected ECM fungi, see Online Resource 3.…”
Section: Discussionmentioning
confidence: 99%
“…For molecular identification of fungal taxa, 1-5 root tips of each distinct ECM morphotype per each seedling provenance were placed in 1.5 ml centrifugation tubes and stored at -16°C . DNA extraction and PCR using primers ITS1F and ITS4 (White et al, 1990) were conducted as in a previous study (Menkis and Vasaitis, 2011). Sequencing was performed by Macrogen Inc., Seoul, Korea and raw sequence data were analysed using the SeqMan Pro version 9.1.0 software from the DNASTAR package (DNASTAR, Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, intensive management practices (often fertilization, application of pesticides for weed and pest control, etc.) in forest nurseries may often result in both reduced ECM colonisation of seedling roots and species diversity (Nilsson and Wallander, 2003), and only a limited number of ECM fungi can tolerate such growth conditions (Menkis and Vasaitis, 2011). A number of studies have shown importance of host genotype to richness and abundance of ECM fungi associated with seedling roots (Korkama et al, 2006;Leski et al, 2010;Velmala et al, 2013), indicating that selection of particular tree genotype or seed provenance may improve ECM colonisation of seedling roots and eventually their better performance after outplanting.…”
Section: Introductionmentioning
confidence: 99%